Obrigatoriedade da educação infantil a partir de quatro anos de idade: percepções de educadores e familiares - Marchetti, Rafaela (Universidade Federal de São Carlos, 2015)
This writing addresses three important perspectives: the cycle of Public Policy in Early Childhood Education, in order to understand how it was constituted in Brazil; the reflection on some of the conceptions about Children and Child, intending to understand how the contemporary society conceptualizes them; and investigate how was the process of discussion, drafting and enactment of the Law 12,796 / 13, which obligates children of four years old to be in a school, highlighting issues on the right and the obligation concerning Education. Such perspectives served to trace the research objective, which was to identify the vision of these professionals (managers, teachers, staff) and some families who has children in public schools, and their theoretical conceptions and practices about the implementation of the Law 12,796 / 13. The research has an empirical part performed through semi-structured interviews in three municipal schools of the State of São Paulo. For the analysis, we chose two categories: the professionals and family´s view of education, after the Law 12,796 / 13. In this case, the theoretical concepts were divided into two subcategories: "conceptions of childhood and child"; and "public policies for early childhood education: law and obligation . In a second instance, it refers to a professional view of education and family, in relation to the existence of possible changes in Early Childhood Education, after the Law 12,796 / 13. This was also divided into two subcategories: "Pedagogical Work: teaching and learning" and "Relations between school and family." The participants were not so surprised by the Law 12,796 / 13, and with the issue of right and obligation at the same time, they were not informed about everything that involved a mixture of agreement with the changes in society and the lack of further discussion. Presented on the social function, the concepts were analyzed, such as the child's socialization and the possibility of their autonomy, with a view of the socially accepted behavior, or limits. For the interviewed ones, the child's social life only begins at the moment that enters the school environment, and as soon as that happens, it will have less difficulty in teaching and learning process and in their schooling. For teachers, the improvement of the education quality was centered on family activities with their young children. In this way, the solution to their improvement was intrinsically related to the family.The school being exempted from this commitment. However the family puts their hopes in school education as something that changes the future of their children, which can improve their economic conditions such as work or employment, without questioning their educational and pedagogical actions, as something normal or "natural" . Calls out our attention to the omission of the participants regarding children 0-3 years of age, that is, the babies were not remembered, and not even mentioned, as if the Early Childhood Education started only 4 years old (due to mandatory) and the concernn was restricted mainly to those who were completing 6 years of age due to proximity to the elementary school of the initial series.
Keywords: Educação infantil; Percepção; Políticas públicas educacionais; Direito à educação; Obrigatoriedade escolar; Early childhood education; Perception of educators and family; Educational public policy; Compulsory school; CIENCIAS HUMANAS::EDUCACAO